Teaching Reading Strategies for Vocational High School - Rohmawati Rohmawati; John Pahamzah; Syafrizal Syafrizal (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2022)
The aims of this research were to find out the English learning strategies for students at the second years students of SMKN 1 Kramatwatu and the students reading progress after having their own strategy in enhancing their reading comprehension. In this research, the researcher used qualitative research by implementing a case study research, which is more emphasize social reality as something intact complex, dynamic, and interactive, to examine the condition of natural objects. Based on the finding of the research indicated that there are some difficulties faced by the students, namely limited vocabulary mastery so that it affected students in understanding reading. Based on the problems, the teacher used two pre-reading strategies: contextual redefinition and word list to help students understood the contents of a reading text. Based on the results of the analysis data, it was found that two-pre reading strategies: contextual redefinition and word list could help students in understanding a reading text, increased vocabulary mastery, and increased students motivation in reading. On the other hand, there were changes in student second year, the students who achieve more than minimum scores. It can be concluded that: firstly, the students’ difficulty in understanding reading is influenced by the lack of mastery of vocabulary and low motivation to learn. Secondly, the use of contextual redefinition and word lists makes it easy for students to find out the meaning of a reading with vocabulary and context.